(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper is an attempt to explore the contribution of literature in promoting sustainable development. Various literary works are critically analysed to examine how literature can raise awareness about environmental issues, promote social justice, gender equity and inspire individual and collective action towards sustainability. Literature can be considered as the mother of all knowledge. It is made of the life experiences. It has the power to shape our perceptions, values, and behaviors. The United Nations have framed 17 Sustainable Development Goals (SDGs). Literature can play a crucial role in attaining these goals as literature is closely related to culture. And both literature and culture are connected to sustainability. By investigating the connections between literature, culture, and sustainability, this paper exhibits the potential of literature to contribute to a more equitable and environmentally conscious world.